Green solutions for mango insect pest management: A bio-rational perspective - Singh, H S; Routray, S; Singh, Deepak (Indian Horticulture, 2026)
Mango crops are affected by numerous insect pests, primarily hoppers, fruit flies, mealy bugs, borers, and thrips. Extensive use of chemical pesticides has led to pest resistance, resurgence, residue accumulation, and environmental pollution. This necessitates the adoption of environmentally friendly, bio-rational pest management practices. Bio-rational pest management relies on biodegradable,target-specific, and residue-free options, such as cultural, botanical, microbial, mechanical, and ICT-based approaches. Successful pest management in mango orchards depends on the correct application of multiple strategies, including orchard sanitation, pruning, neem formulations, microbial bio-pesticides, pheromone traps, and bio-agent applications. Digital and online tools, combined with "smart traps," IoT, and remote monitoring, enhance early warning systems, precision, and decision-making, supporting ecologically sound, economically viable, and sustainable protection strategies for mango orchards.